2014
DOI: 10.1152/jn.00543.2013
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting the roles of the supplementary and frontal eye fields in ocular decision making

Abstract: Single-unit recording in monkeys and functional imaging of the human frontal lobe indicate that the supplementary eye field (SEF) and the frontal eye field (FEF) are involved in ocular decision making. To test whether these structures have distinct roles in decision making, single-neuron activity was recorded from each structure while monkeys executed an ocular go/nogo task. The task rule is to pursue a moving target if it intersects a visible square or "go zone." We found that most SEF neurons showed differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…2011a; Mahaffy and Krauzlis ). These results indicate that, although both areas are involved in smooth‐pursuit prediction, the SEF is primarily involved in planning based on cue‐information memory, whereas the FEF is primarily involved in generating motor commands for efficient pursuit execution (also Yang and Heinen ). Involvement of FEF pursuit neurons in extra‐retinal pursuit components has been shown using a single spot (Tanaka and Fukushima ; Fukushima et al.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…2011a; Mahaffy and Krauzlis ). These results indicate that, although both areas are involved in smooth‐pursuit prediction, the SEF is primarily involved in planning based on cue‐information memory, whereas the FEF is primarily involved in generating motor commands for efficient pursuit execution (also Yang and Heinen ). Involvement of FEF pursuit neurons in extra‐retinal pursuit components has been shown using a single spot (Tanaka and Fukushima ; Fukushima et al.…”
Section: Discussionmentioning
confidence: 88%
“…FEF inactivation, in contrast, did not induce such errors but decreased pursuit eye velocity during pursuit maintenance, resulting in "saccadic tracking" (Fukushima et al 2011a;Mahaffy and Krauzlis 2011). These results indicate that, although both areas are involved in smooth-pursuit prediction, the SEF is primarily involved in planning based on cue-information memory, whereas the FEF is primarily involved in generating motor commands for efficient pursuit execution (also Yang and Heinen 2014). Involvement of FEF pursuit neurons in extra-retinal pursuit components has been shown using a single spot (Tanaka and Fukushima 1998;Fukushima et al 2000Fukushima et al , 2002 and during memory-based pursuit (Fukushima et al 2011a).…”
Section: Neural Correlates For the Extra-retinal Mechanisms To Initiamentioning
confidence: 83%
“…DMFC is a natural candidate for our task because it plays a crucial role in timing as shown by numerous studies in humans (Halsband et al 1993;Rao et al 2001;Coull et al 2004;Pfeuty et al 2005;Macar et al 2006;Cui et al 2009) , monkeys (Okano & Tanji 1987;Merchant et al 2013;Kunimatsu & Tanaka 2012;Isoda & Tanji 2003;Romo & Schultz 1992;Merchant et al 2011;Mita et al 2009;Ohmae et al 2008;Kurata & Wise 1988) , and rodents (Matell et al 2003;Kim et al 2009;Smith et al 2010;Kim et al 2013;Xu et al 2014;Murakami et al 2014) , and because it is involved in context-specific control of actions (Isoda & Hikosaka 2007;Ray & Heinen 2015;Yang & Heinen 2014;Shima et al 1996;Matsuzaka & Tanji 1996;Brass & von Cramon 2002) .…”
Section: Neural Activity In the Rsg Taskmentioning
confidence: 99%
“…Rather, many other findings suggest that they can be understood as monitoring performance of tasks . The SEF contributes to abstract representations and dispositions that facilitate the performance of complex tasks (Amador et al 2004, Moorman & Olson 2007, Stuphorn et al 2010, Yang et al 2010, Kunimatsu & Tanaka 2012 to a greater extent than the FEF does (Heinen et al 2011, Middlebrooks & Sommer 2012, Yang & Heinen 2014). In addition, many studies have found that SEF and ACC neurons signal negative (error) and positive (reward) feedback (Amador et al 2000, Stuphorn et al 2000, Ito et al 2003, Matsumoto et al 2007, Uchida et al 2007, Kuwabara et al 2014, So & Stuphorn 2012, Purcell et al 2013, Shen et al 2014.…”
Section: Medial Frontal Cortexmentioning
confidence: 99%